The Judgment of the CJEU of 25 July 2018 on Mutagenesis: Interpretation and Interim Legislative Proposal - Vives-Vallés, Juan Antonio; Collonnier, Cécile (Frontiers in Plant Science, 2020)
The Judgment of 25 July 2018 of the Court of Justice of the European Union (CJEU) was optimistically awaited by breeders and supporters of agricultural biotechnology, but short after the press release advancing the Judgment, hope turned into frustration. Opinions on how to frame the New Breeding Techniques (NBT) in the context of Directive 2001/18/EC were issued before the Judgment, while proposals to assist the EU legislator to amend the regime driven by the Directive have been also provided afterwards by scholars and institutional bodies around the EU. However, not so much attention seems to have been paid to the Judgment itself. Through legal analysis, this paper tries to determine the very meaning of the Judgment. It finds out that while the impacts of the Judgment on the NBT might have been slightly overvalued, its potential negative effects on techniques of random mutagenesis and varieties breed through them have been generally underestimated if not absolutely overlooked. The analysis also shows that the Judgment does not preempt the possibility to exempt some NBT from the scope of Directive 2001/18/EC, and in fact ODM, SDN1 and SDN2 might be, under certain conditions, easily exempted from its scope by the EU legislature without the need of a deep legislative revolution nor even the amendment of Directive 2001/18/EC. As regards techniques of random mutagenesis and mutant varieties bred by means of those techniques, until action is taken by Member States (if finally taken), no real limitations upon them are to be feared. However, if Member States start to consider the path opened by the CJEU, then their regulation at an EU level should be readily explored in order to avoid further negative effects on plant breeding as well as on the free movement inside the EU of those varieties and the products elaborated thereof.